FEMALE ROLE CONFLICT : THE IMPACT OF LAMAHOLOT CULTURE AND WORKING ENVIRONMENT IN IKAT WEAVING CRAFTERS IN THE FLORES EASTERN DISTRICT - Dua Nurak, Lucia Adinda; Sudibya, Gde Adnyana; Riana, Gede (Buletin Studi Ekonomi; VOL.19.NO.1.FEBRUARI 2014.(PP 1-117), 2016)
Female Role Conflict : The Impact of Lamaholot Culture and Work Environment in Ikat Weaving Crafters in The Flores Eastern District. The development has resulted in a paradigm change of the women role in the social order at the society. The role change has an impact to the environment as a result of conflict and culture. This study is aimed to obtain the cultural influences and the working environment to role conflict. The samples of the research are 98 women who worked on the public sector. The data was collected by interview and questionnaire, then analyzed by Structural Equation Modeling (SEM) using SmartsPLS. Analysis results showed that the culture has a positive and significant effect to the working environment, culture has a positive effect but not significant on role conflict, and the working environment has a negative and significant effect on role conflict of women who work at the public sector.   Keywords : conflict, culture, work environment
Keywords: conflict, culture, work environment